Developing competences in a cross-border interdisciplinary project: student and teacher perceptions of the Ocean i3 project - Gil-Molina, Pilar; Cruz-Iglesias, Esther; Rekalde-Rodríguez, Itziar (Journal of University Teaching and Learning Practice, 2024)
The aim of this research was to analyse students’ perceptions of the competences developed by taking part in the cross-border interdisciplinary Ocean i3 project. The objective of the Ocean i3 project is for students to acquire learning, research and sustainability competences while contributing to reduce plastic pollution along the Basque-Aquitaine coast. The project uses a Challenge-Based Learning approach in which social actors from the surrounding cross-border area propose challenges that students have to solve. The research methodology used is exploratory and descriptive; for the data collection qualitative and quantitative instruments have been used. The main result is that students and teachers perceive that the former have improved the sustainability competences engaging and working on the project. Mostly they perceive to have developed active listening, analysis, creativity and negotiation competences.